The organization of information - Taylor, Arlene G. (Libraries Unlimited, 2004)
This book provides students, practicing librarians, and others interested in information organization with a clear discussion of the theory, principles, standards, and tools behind the organization of information in all variety of information environments, primarily libraries. Covers the different environments; the formats of functions of retrieval; the history of basic principles; encoding standards; systems and system design; metadata (a new chapter); access points and authority control; subject approaches to organizing information; concepts involved in determining "aboutness"; and arrangement and display.